1989
DOI: 10.3181/00379727-191-42932
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experimental Obesity and Subsequent Weight Reduction upon Circulating Atrial Natriuretic Peptide

Abstract: The effect of obesity and weight reduction upon circulating concentrations of atrial natriuretic peptide was assessed in an experimental model of the disease. Obese rats weighing in excess of 750 g were compared with formerly obese animals subjected to a 15-week period of caloric restriction resulting in a 40% reduction in body weight. Mean adipocyte size was significantly reduced with weight loss, as was estimated body fat. Mean arterial blood pressure remained normotensive for both groups, but a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 10 publications
2
11
0
2
Order By: Relevance
“…Therefore, for the first time, we demonstrated that, in humans, calorie intake and body weight are important modulators of the humoral, renal, and hemodynamic effects not only of exogenous ANP but also of the endogenous NP system. Our findings are in agreement with those of Crandall et al, 25 showing that, in experimental obesity, diuresis and natriuresis accompanying weight reduction may be due to increased activity of ANP.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, for the first time, we demonstrated that, in humans, calorie intake and body weight are important modulators of the humoral, renal, and hemodynamic effects not only of exogenous ANP but also of the endogenous NP system. Our findings are in agreement with those of Crandall et al, 25 showing that, in experimental obesity, diuresis and natriuresis accompanying weight reduction may be due to increased activity of ANP.…”
Section: Discussionsupporting
confidence: 83%
“…24 Finally, in experimental obesity, weight reduction might facilitate ANP activity, inducing diuresis and natriuresis. 25 These findings are consistent with the hypothesis that the abundance of clearance receptors in the total adipose mass of obese hypertensives might play some role in obesity-related hypertension by reducing the biological activity of circulating ANP.…”
supporting
confidence: 81%
“…In an experimental study with obese rats and subsequent weight reduction through caloric restriction, Crandall et al [12] found that circulating atrial NP levels were significantly elevated after a 40% reduction in body weight. Furthermore, an analysis of heart-to-body weight ratios showed that an obesity-associated, volume-induced cardiac hypertrophy remained even after normalization of body fat.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, cardiac cachexia is known to be an independent predictor of decreased survival [11]. Furthermore, there is evidence that circulating lipoproteins in obese patients may bind and detoxify the lipopolysaccharides that play a role in stimulating inflammatory cytokines [12].…”
mentioning
confidence: 99%
“…24,25 In experimental animals, caloric deprivation through fasting results in dramatic decreases in NPR-C gene expression 26 and increased circulating ANP levels. 27 Elevated NPR-C gene expression has been documented in the adipose tissue of humans with obesity and hypertension, 5 and allelic variants of this gene have been associated with lower plasma natriuretic peptide levels. 28 Reduced secretion of natriuretic peptides from diminished myocardial hormone release 6 or impaired synthesis 29 may also be an important explanation for low plasma natriuretic peptide levels.…”
Section: Mechanisms For Reduced Natriuretic Peptide Levels In Obesitymentioning
confidence: 99%